2014
DOI: 10.1093/jpids/piu079
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Associations Between Short-Bowel Syndrome and Bloodstream Infection Among Hospitalized Children

Abstract: While several clinical characteristics are contributory to the risk of BSI in children, SBS remains the single strongest predictor. Further research into the mediators of this risk will be essential for the development of prevention strategies for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…For example, pediatric patients with short gut syndrome, who are dependent upon parenteral nutrition, are at high risk for recurrent central line infections and thus may have higher cumulative antibiotic exposure than even some critical care and oncology patients. [34][35][36][37] For such patients, pathogens causing CLABSIs may be more likely to be antibiotic resistant. Other potential explanations include differences in infection control practices or opportunities for transmission in pediatric ward locations compared to critical care or oncology locations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pediatric patients with short gut syndrome, who are dependent upon parenteral nutrition, are at high risk for recurrent central line infections and thus may have higher cumulative antibiotic exposure than even some critical care and oncology patients. [34][35][36][37] For such patients, pathogens causing CLABSIs may be more likely to be antibiotic resistant. Other potential explanations include differences in infection control practices or opportunities for transmission in pediatric ward locations compared to critical care or oncology locations.…”
Section: Discussionmentioning
confidence: 99%
“…CVCs are ubiquitous in patients with intestinal failure as a means for survival in patients who require PN and/or fluids to allow appropriate growth and development. Short bowel syndrome was the single strongest predictor for risk of bloodstream infections in a retrospective review of 40,723 pediatric hospital admission with 1047 diagnoses of bloodstream infections, in which 20% included a short bowel syndrome diagnosis 94 . In a systemic review of patients with intestinal failure, ethanol vs heparin locks have been shown to be more effective at reducing the number of CLABSIs as well as reducing the rate of catheter removals 95 .…”
Section: Prevention Strategies—ethanol Lock Therapymentioning
confidence: 99%
“…Children with SBS are at high risk for ambulatory central line–associated bloodstream infection (A‐CLABSI) because of prolonged requirement for central lines (CLs) to deliver home parenteral nutrition (HPN) . A‐CLABSI differs from healthcare‐associated central line–associated bloodstream infection (HAI‐CLABSI) in characteristics and risk factors . Children with SBS and malignancy are the main populations at risk for A‐CLABSI, as both require prolonged central access.…”
Section: Introductionmentioning
confidence: 99%
“…Children with SBS and malignancy are the main populations at risk for A‐CLABSI, as both require prolonged central access. Indeed, 46% of hospitalizations of children with SBS are due to A‐CLABSI, representing 20% of all admissions due to bloodstream infection (BSI) in pediatrics . Furthermore, A‐CLABSI was found 3 times more commonly than HAI‐CLABSI in pediatric oncology patients, and 13% of their admissions were to the pediatric intensive care unit .…”
Section: Introductionmentioning
confidence: 99%